Il SIT di ACEA ATO2 per il controllo del sistema idrosanitario - De Felice, Mauro; Tosto, Cesare (GEOmedia, 2009)
Hydrosanitary system control through ACEA ATO2 Geographic Information System The urban water networks management through a GIS can highlites the complexity of such structures. The models used inside the system can be used to manage water flows and to minimise leaks or illegal access. Intergraph's Portfolio of products offer easy-to-use capabilities that cover the entire workflow from damage management to maintenance operations.